Secondary forest within a timber plantation concession in Borneo contributes to a diverse mammal assemblage - William, Wilvia Olivia *; van Manen, Frank T.; Sharp, Stuart P.; Ratnayeke, Shyamala * (Elsevier, 2023)
Commercial tree plantations of fast-growing species have become increasingly important in Southeast Asia to meet global demand for wood and wood fiber products. There is a growing need to understand more about their value for wildlife and how they can be managed for biodiversity. We evaluated the effects of landscape attributes on mammal communities in a timber concession consisting of 83 % secondary forest and 17 % tree plantations in northern Sabah, Malaysia. Using camera traps, we compared mammalian species assemblages of secondary forest and commercial tree plantation stands and identified habitat predictors associated with total mammal species detections and species richness in the landscape mosaic. We used 87 camera stations deployed for 23 days across two major land-use types: 62 sites in secondary forest (previously logged natural forest) and 25 sites in tree plantations. We evaluated variation in species richness in these two major land-use categories and assessed the effects of natural and anthropogenic predictors on variation in total mammal detections and species richness. We detected at least 23 large and medium-sized mammal species over 2035 trap nights. Fourteen of those species were classified as threatened or near-threatened by the International Union for the Conservation of Nature. Rarefaction did not reveal differences in mammal species richness or diversity between camera sites placed in tree plantations and secondary forests, likely because most camera sites in tree plantations were close to secondary forest and comprised < 30 % of all sites. However, generalized linear models indicated lower mammal diversity as proportions of tree plantation and proximity to human settlements increased. Total mammal records, including those of threatened mammals, increased with greater proportions of secondary forest. Retention of larger tracts of secondary forest around plantation areas appears to be important to maintain mammalian species richness and contributes to the conservation value of commercial timber plantations. These findings may assist in the management of mammals of conservation concern and implementation of adaptive management plans to enhance biodiversity conservation in commercial plantations.